2009
DOI: 10.1159/000223419
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of GH-Treated Girls with Turner Syndrome: Metabolic Consequences

Abstract: Aims: To investigate the metabolic consequences of long-term GH treatment in young women with Turner syndrome (TS), several years after GH discontinuation. Methods: Follow-up study of a randomized GH dose-response trial, with 3 GH dosages (1.3, 2.0, and 2.7 mg/m2/day). Thirty-nine TS patients (20.0 ± 2.1 years) participated 4.8 ± 1.9 years after GH discontinuation. Mean GH treatment duration was 8.7 ± 2.0 years. Fasting glucose, insulin, and serum lipids were measured. Results: Several years after G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 53 publications
3
20
1
3
Order By: Relevance
“…In accordance with our findings, several other studies found that insulin sensitivity decreased during GH therapy [6,9,26,27,28]. These studies showed that after discontinuing GH therapy, insulin sensitivity indices either returned to pre-treatment levels [27], or decreased to values just above baseline but comparable with those of healthy post-pubertal girls [29]. In our study, the indices returned to pretreatment levels, confirming the reversibility of the effect of GH on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our findings, several other studies found that insulin sensitivity decreased during GH therapy [6,9,26,27,28]. These studies showed that after discontinuing GH therapy, insulin sensitivity indices either returned to pre-treatment levels [27], or decreased to values just above baseline but comparable with those of healthy post-pubertal girls [29]. In our study, the indices returned to pretreatment levels, confirming the reversibility of the effect of GH on insulin sensitivity.…”
Section: Discussionsupporting
confidence: 92%
“…During the last decade many studies showed growth hormone (GH) treatment as safe and effective for growth promotion in TS. Table 2 presents the results of growth therapy and indicates positive, negative and neutral determinants of therapy effectiveness as well as consequences and side effects of hormonal therapy in the analysed articles (4,5,7,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50).…”
Section: Growth and Growth Therapy And Consequencesmentioning
confidence: 99%
“…Some studies have reported the improvement of some lipid profile parameters, such as decrease in lipoprotein A, apoprotein A-I and increase in HDL cholesterol after the beginning of estrogen replacement. The administration of rhGH also improves the lipid profile by reducing total cholesterol and LDL cholesterol and increasing HDL (41,43). Androgen replacement therapy presents controversial effects on lipid metabolism in patients with TS.…”
Section: Cardiovascular Riskmentioning
confidence: 99%